Trichloroacetic Acid Peeling for Treating Photoaging: A Systematic Review - Irma Bernadette S. Sitohang; Lili Legiawati; Lis Surachmiati Suseno; Fadhila Dea Safira (Hindawi Limited, 2021)
Photoaging can significantly contribute to lower quality of life. Medium-deep peeling using trichloroacetic acid allows controlled keratocoagulation through the dermis and into the dermal papillary layer that is effective for skin rejuvenation. The purpose of this article is to give updates regarding the efficacy, possible adverse events, and patient satisfaction of trichloroacetic acid (TCA) peeling for skin rejuvenation by assessing various photoaging parameters. A systematic review of prospective trial articles collected from PubMed, MEDLINE, EMBASE, Cochrane, and Scopus databases was conducted on November 2, 2020. Treatment efficacy was assessed based on the photoaging parameters used by each study. Adverse events and patient satisfaction as the secondary outcome were assessed based on patients-perceived improvements. Five studies included three randomized comparison studies and two prospective cohort studies. These studies show that TCA peeling significantly improve the cosmesis of photoaged facial skin. Low concentration is effective for superficial sun damage. Medium-depth peels using a higher concentration of TCA or as combination therapy are effective as skin resurfacing agents to reduce wrinkles. Some adverse effects may occur but usually resolve within weeks. Overall patients were satisfied with the treatment result. An equivalent basic skin preparation such as topical retinoic acid skin priming prior to intervention is necessary for more objective comparison. Further research studies with a larger sample size and longer follow-up period are required. This evidence suggests that TCA peeling is effective in photoaging treatment, either as monotherapy or as combination therapy with other modalities.